1979
DOI: 10.1111/j.1469-8986.1979.tb01430.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Level of Socialization on Electrodermal Detection of Deception

Abstract: Fifteen college students attempted to deceive a professional polygraph examiner, while 15 others who had nothing to hide also submitted to the examination. The examiner was blind as to whether each subject was deceptive or truthful. Using the skin conductance response (SCR), significant discrimination was made between deceptive and truthful subjects with both “guilty person” and “guilty knowledge” polygraph tests. On both types of test, however, subjects who were not detected were significantly less socialized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…Our results further demonstrate that antisocial inmates display reduced electrodermal responding to concealed information. This finding is consistent with the results of two experiments by Waid and colleagues (1979a, 1979b), who also observed reduced skin conductance responding to concealed information in low socialized undergraduates (but see Balloun & Holmes, 1979; Gudjonsson, 1982). Raskin and Hare (1978) noted that lack of responding to concealed information results in a truthful outcome (e.g., a false negative outcome).…”
Section: Main Studysupporting
confidence: 91%
See 1 more Smart Citation
“…Our results further demonstrate that antisocial inmates display reduced electrodermal responding to concealed information. This finding is consistent with the results of two experiments by Waid and colleagues (1979a, 1979b), who also observed reduced skin conductance responding to concealed information in low socialized undergraduates (but see Balloun & Holmes, 1979; Gudjonsson, 1982). Raskin and Hare (1978) noted that lack of responding to concealed information results in a truthful outcome (e.g., a false negative outcome).…”
Section: Main Studysupporting
confidence: 91%
“…Using skin conductance responses, no differences in detection rate were found between high and low antisocial individuals. In two other studies (Waid, Orne, & Wilson, 1979a, 1979b) undergraduates, half of which had enacted a mock crime, were engaged in a concealed information test. In both studies, the socialization scale of the California Psychological Inventory (Gough, 1956) was administered.…”
mentioning
confidence: 99%
“…Lykken (1957) found lower overall electrodermal response amplitudes in sociopathic individuals. Later studies found personality traits such as the “level of socialization” (Waid, 1976; Waid et al, 1979; Waid and Orne, 1980, 1981) to be correlated with differential physiological responding in the CIT and the detection of deception in general.…”
Section: Introductionmentioning
confidence: 99%
“…Lykken (1957) found lower Frontiers in Psychology | Cognitive Science overall electrodermal response amplitudes in sociopathic individuals. Later studies found personality traits such as the "level of socialization" (Waid, 1976;Waid et al, 1979;Waid andOrne, 1980, 1981) to be correlated with differential physiological responding in the CIT and the detection of deception in general.…”
Section: Personality Aspects In the Citmentioning
confidence: 99%